Materials and modes of translation: Re-imagining inclusive “zero”-waste futures - van den Eijnden, Tamalone; Baibarac-Duignan, Corelia; de Lange, Michiel; de Goede, Maartje (Frontiers in Sustainable Cities, 2022)
In this paper, we present and reflect upon a creative and participatory approach to engaging citizens in imagining desirable ‘zero’-waste futures that include different values and perspectives. The approach emerged through a four-month collaboration involving academic researchers and creative professionals, and was prototyped in a formerly industrial neighbourhood of Utrecht (het Werkspoorkwartier), currently being developed as a creative circular manufacturing area. In doing so, we will provide alternatives to abstract technology-centered policy visions that portray issues of waste as objective and somewhat isolated challenges that can be addressed through data-driven technological solutions, smoothing out any potential frictions that may result from implementing them. This provides only a narrow vision of how the future might look like, neglecting many other perspectives and values, while also not paying sufficient attention to the process of imagination. To gather and articulate different perspectives on alternative ‘zero’-waste futures, we focus on citizen science-inspired methods to engage people and stimulate imagining futures that address different values. We work in close collaboration with creative practitioners, both in terms of anchoring the research in a real-world context, and also in terms of combining our different types of expertise to develop the methods. Reflecting on the overall approach, in our paper we discuss the potential of a transdisciplinary approach and coproduced methods to intervene in how we see and imagine alternative futures by taking ‘translation’ as an analytical lens to understand how different meanings are created with experiential, material and affective modes of expression. Specifically, we will analyse the translations that occur in processes of moving from abstract data to matters of concern and from desirable futures to actionable presents. Looking at these multiple processes through the lens of translation will serve to investigate how different future imaginaries are generated through different materials and modalities of translation, offering different forms of engagement in shaping inclusive urban futures. Translation here will be conceptualized less as a perfect transference of information and more as an open-ended process of paying attention to different values, and identifying those matters for which to care for in our urban futures